2020
DOI: 10.2196/18174
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Smartphone App on the Quality of Pediatric Colonoscopy Preparations: Randomized Controlled Trial

Abstract: We state that In total, 46 patients aged 5-18 years "received either app-based or written material with instructions on how to take their prep medications as well as information about the colonoscopy procedure." Prep quality, number of calls to the gastroenterology service, and patient arrival time were recorded. After the procedure, a questionnaire was given to each patient in which they graded their knowledge of the procedure both before and after receiving the app or written material. 1b-ii) Level of human … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…One of the eight studies was based on a pediatric population. [ 10 ] Most of the included studies focused on the adult population. The methodology was consistently randomized controlled, prospective, single-blinded trials except for one study, which was a feasibility study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the eight studies was based on a pediatric population. [ 10 ] Most of the included studies focused on the adult population. The methodology was consistently randomized controlled, prospective, single-blinded trials except for one study, which was a feasibility study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Two of the eight studies were done in the United States. [ 10 12 ] and the remaining were internationally based. The median number of patients involved was 210 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Maxwell et al (111) measured bowel preparation quality and found no significant benefit of using an educational cartoon over the standard instructions. Brief et al (112) demonstrated better quality preparations in pediatric patients who received their instructions via a smartphone application compared to standard written instructions. Studies of adult patients have also demonstrated superiority of smartphone apps to deliver prep instructions and education (113,114).…”
Section: Facility Subdomain 2: Quality Of Patient and Caregiver Exper...mentioning
confidence: 99%
“…A RCT evaluating the impact of an educational cartoon did not show improved Ottawa Bowel Preparation Scale (OBPS) scores in the 20 patients who received the cartoon, but the study did report a positive correlation with education level and quality of bowel preparation ( 4 ). A recent study of 42 patients applied the use a Smartphone App to deliver colonoscopy tutorial, instructions, and medication reminders ( 5 ). This study showed improved bowel clean out scores in the 20 patients who used the App.…”
Section: Patient Educationmentioning
confidence: 99%